Marketing Plan Rica Roa Minyak Kelapa “ROKLA” - Tri Utami Suharto; Nancy Henrieta Jesamine Mandey; Wingston Markus Jusuf Longdong; Mikke Marentek (Universitas Merdeka Madiun, 2024)
The culinary business world is currently developing very rapidly, especially in the city of Manado, which has great potential for hot chilli sauce products such as Rica Roa. The “Rokla” business comes with innovation using pure coconut oil (VCO), which is known to be healthier than the copra coconut oil that is generally used. This chilli sauce not only has a distinctive spicy taste, but also offers a unique taste thanks to the us of VCO. However, this business still in the early development stage,so it requires careful marketing planning. For this reason, a SWOT analysis is carried out to identify the strengths, weaknesses, opportunities and threats facing this business. Apart from that, the IFAS and EFAS matrices are also used to deepen the analysis and find the most appropriate marketing strategy. After analysing the SWOT, the STP (Segmenting, Targeting and Positioning) strategy is applied to determine the appropriate target market. Next, the 4P marketing mix (Product, Price, Place, Promotion) is used to implement the strategy that has been formulated. With this approach, it is hoped that the “Rokla” business can expand its market reach and increase its competitiveness, especially through digital promotion strategies and expanding distribution to various potential market segments.